Diabetes mellitus in stable chronic heart failure and the combination with humoral activation, their association, and prediction of 2-year adverse outcomes. Data from the FAR NHL registry - Labr, Karel; Spinar, Jindrich; Parenica, Jiri; Spinarova, Lenka; Krejci, Jan; Malek, Filip; Ostadal, Petr; Ludka, Ondrej; Jarkovsky, Jiri; Benesova, Klara; Labrova, Ruzena; Spinarova, Monika (Journal of diabetes, 2024)
BACKGROUND/AIM: The study aims to describe the role of diabetes in patients with heart failure. METHODS: In all, 1052 chronic heart failure patients were included in the FARmacology and NeuroHumoral Activation (FAR NHL) multicenter prospective registry. They had ejection fraction below 50% and were on stable medication for at least 1 month. RESULTS: More than one-third (38.9%) of the patients had diabetes mellitus (DM). Diabetic patients (N = 409) were older (median 67 vs. 64, p < 0.001), had higher body mass index (BMI) (30 vs. 28 kg/m2, p < 0.001), much more frequently had ischemic heart disease (71 vs. 47%, p < 0.001), hypertension (80 vs. 67%, p < 0.001), dyslipidemia (89 vs. 69%, p < 0.001), worse renal function (estimated glomerular filtration rate [eGFR] median 63 vs. 73 mL/min/1.73 m2, p < 0.001), and higher N-terminal pro-brain natriuretic peptide (NT-proBNP) (median 681 vs. 463 pg/mL, p = 0.003). All-cause death, left ventricle assist device implantation, and orthotopic heart transplantation were set as the combined primary end point, which was present in 15.5% (163 patients) within the 2-year follow-up. In the 2-year follow-up, 81.0% of patients with diabetes survived without a primary end point, while 85.4% of the patients without diabetes survived, the difference being on the verge of statistical significance (p = 0.089). DM is a statistically significant predictor of NT-proBNP value in univariate analysis, but it is not an independent predictor in a multivariate analysis. When the NT-proBNP level was high, the presence of DM did not influence the prognosis. CONCLUSION: The combination of diabetes and NT-proBNP levels may better stratify the prognosis of patients with chronic heart failure.
Keywords: Female; ženské pohlaví; Heart Failure; Registries; diabetes mellitus; lidé; srdeční selhání; Natriuretic Peptide, Brain; prognóza; peptidové fragmenty; natriuretický peptid typu B; prospektivní studie; Male; Peptide Fragments; Aged; Prospective Studies; Prognosis; chronická nemoc; Diabetes Mellitus; lidé středního věku; registrace; senioři; mužské pohlaví; Chronic Disease; Middle Aged; Humans